2011
DOI: 10.1510/icvts.2010.265116
|View full text |Cite
|
Sign up to set email alerts
|

Highly flexible nitinol mesh to encase aortocoronary saphenous vein grafts: first clinical experiences and angiographic results nine months postoperatively

Abstract: Saphenous vein graft patency is frequently limited by degeneration. Experimental studies have indicated that rigid external support of venous grafts by a flexible, tubular nitinol mesh may improve graft patency. The study presented was part of a prospective, randomized, multicenter first-in-man trial investigating the safety and effectiveness of nitinol-supported venous grafts in coronary artery bypass graft (CABG) surgery. From our clinic, 25 subjects with multivessel coronary artery disease requiring sapheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 19 publications
0
38
0
Order By: Relevance
“…However, limited clinical data has been published to date with such devices. Murphy et al (14) described 100% occlusion of externally stented SVGs at six months and Schoettler et al (15) reported a 72% occlusion rate at nine months. Recently, Rescigno et al (16) described 66.9% occlusion at 12 months of SVGs supported with nitinol mesh.…”
Section: Introductionmentioning
confidence: 99%
“…However, limited clinical data has been published to date with such devices. Murphy et al (14) described 100% occlusion of externally stented SVGs at six months and Schoettler et al (15) reported a 72% occlusion rate at nine months. Recently, Rescigno et al (16) described 66.9% occlusion at 12 months of SVGs supported with nitinol mesh.…”
Section: Introductionmentioning
confidence: 99%
“…Prior attempts to externally support vein grafts involved the use of fibrin glue and sutures to fixate the external support to the vein graft [15,16]. Experimental data have shown that the application of fibrin glue on the external surface of vein grafts lead to aneurysmal degeneration and excessive intimal hyperplasia which may have jeopardized vein graft patency [17][18].…”
Section: Resultsmentioning
confidence: 99%
“…Experimental data have shown that the application of fibrin glue on the external surface of vein grafts lead to aneurysmal degeneration and excessive intimal hyperplasia which may have jeopardized vein graft patency [17][18]. Recent clinical data showed that suturing and fixating an external support device to the anastomoses leads to early failure of vein grafts, most probably due to an acute constriction of the anastomosis site [15]. Application of the FRAME device does not require the use of fibrin glue or any other fixation mechanism postdeployment.…”
Section: Resultsmentioning
confidence: 99%
“…Murphy et al reported 100% occlusion of external stented SVG at 6 months [69]. Schoetler et al reported that the patency rate of mesh-supported SVG was 27.8% at 9 months, whereas conventional SVG showed 85.7% patency [70]. Rescigno et al reported 66.9% occlusion at 12 months of SVG supported with nitinol mesh [71].…”
Section: Cabg Using Saphenous Vein Graftsmentioning
confidence: 99%